You know that (1 + 1/n)^n converges to e
You can easily verify that (1 + a/n)^n and (1+1/n)^(bn) converge.
google can provide proofs.
(1 + a/n)^n = e^a
(1 + 1/n)^(bn) → e^b
So now just combine them. (1 + a/n)^(bn) → e^(ab)
In this case, since e^ln6 = 6, that would be 6^2 = 36
Prove that the sequence: {an} = {(1 + (ln(6)/(n)))^(2n)}infinity n=1 converges
Note:
I don't know how to solve or work out so show all your work. And give the answer in EXACT FORM example 3pi, sqrt(2), ln(2) not decimal approximations like 9.424,1.4242,1232
1 answer